(untitled) (SCHOLARS: Journal of Arts & Humanities, 2026)
This article examines the historical displacement and enduring homelessness of Nepali-speaking Bhutanese refugees through a critical analysis of their poems in exile and post-settlement contexts. The introduction of Bhutan’s “One Nation, One People” policy in the 1980s resulted in the relocation of approximately one hundred thousand Nepali-speaking Bhutanese people. Analyzing poems by Nepali-speaking Bhutanese poets in the light of pertinent historical records and secondary sources, the article investigates how concept of home, belonging, and identity are articulated under the condition of forced migration. This qualitative article employs textual and thematic inquiry into exile, desire for home, liminality and existential uncertainty. The theoretical framework is grounded in Nira Yuval-Davis’s belonging, Avtar Brah’s concept of homing desire, and Homi K. Bhabha’s idea of liminality and third space. One of the key findings is that the Bhutanese Nepali writings consistently represent home as a fractured, relational, and contested construct. It argues that these painful narratives expose a persistent transnational liminal sphere, where political inclusion fails to protect emotional and cultural belonging. This article contributes to refugees and diaspora studies by foregrounding literary expression as a critical site for understanding forced migration, memory, and the politics of belonging beyond the territorial framework.